1999
DOI: 10.7164/antibiotics.52.1143
|View full text |Cite
|
Sign up to set email alerts
|

Tylosin Derivatives. V. Electrochemical Opening of Oxirane Ring.

Abstract: In the preceding paper1} we described the chemical deepoxidation of 1 with dissolving metal (Zn). Reductive oxirane cleavage was accompanied by simultaneous allylic rearrangement giving 1 0, 1 3-dihydro-1 3-hydroxy desmycosin (5). It is noteworthy that preparation of 1 consists of two steps2): oxidation of the 12,13-double bond with mchloroperbenzoic acid with simultaneous formation of TV-oxide, and reduction of the TV-oxide with Ph3P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The advantage of electrochemistry is the ability to precisely control both the potential and rate of the redox process in a manner not possible with conventional chemical oxidants or reductants. For example, electrochemical functionalization has been used to prepare derivatives of the antibiotic tylosin where the modification of the parent compound gives rise to novel desmycosin analogues . Electrochemical oxidation is also a useful tool to understand and study metabolic pathways, as demonstrated for the antimalarial drug amodiaquine .…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of electrochemistry is the ability to precisely control both the potential and rate of the redox process in a manner not possible with conventional chemical oxidants or reductants. For example, electrochemical functionalization has been used to prepare derivatives of the antibiotic tylosin where the modification of the parent compound gives rise to novel desmycosin analogues . Electrochemical oxidation is also a useful tool to understand and study metabolic pathways, as demonstrated for the antimalarial drug amodiaquine .…”
Section: Resultsmentioning
confidence: 99%
“…As a part of the electrochemical derivatisation of macrolide antibiotics [2][3][4][5][6], we carried out the oxidation of 1 with electrogenerated reactive chlorine species in order to introduce chlorine atom into the lactam nitrogen. N-chlorolactam derivative should exhibit conformational changes in comparison with the starting compound what might in a greater or lesser extent affect biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heterogeneous nature of electrode reactions, the reactive intermediates formed in the electrochemical reactions might differ significantly from the intermediates formed in chemical reactions and thus lead to diverse reaction pathways and products, which might be very difficult to prepare by conventional chemical means. The electrochemical methods have already been successfully applied to the electrochemical modifications of macrolide [1][2][3][4][5] and ␤-lactame 6,7 antibiotics.…”
mentioning
confidence: 99%